Policy of Delay: Evidence from a Bayesian Analysis of Metropolitan Land‐Use Choices. Issue 3 (12th November 2016) - Deslatte, Aaron; Tavares, António; Feiock, Richard C.
Abstract : Do local policymakers strategically use delay in permitting development to forestall the growth machine? The mantras of smart growth and sustainable development assume local governments can balance the competing values of economic development, ecology, and equity interests in a community. We employ a political market framework to explain differences in local government land use decisions. This framework conceptualizes policy choices as resulting from the interplay between the aggregate policy demand by residents, developers, and environmental interests and the aggregate supply by government authorities. Delays can be imposed strategically through processes of development approval by city governments where industry strength and form of government vary within county‐level service‐delivery fragmentation. We utilize novel Bayesian multilevel modelling of data collected from 2007 and 2015 surveys of Florida city planners and find strong institutional effects and multilevel relationships.